THE NEED AND IMPORTANCE OF THE PROCESS OF INTEGRATION OF INSURANCE COMPANIES AND COMMERCIAL BANKS - Xudoyberdiyeva Sadoqat Abdumannonova (Journals Park Publishing, 2024)
In the context of globalization of financial services markets, the article analyzes the economic nature of bank insurance services, their classification, mutual services of insurance companies and commercial banks. Also, in the context of the globalization of financial services markets, the advantages of bancassurance services and issues related to foreign experience are explored.
Keywords: commercial banks, insurance companies, bancassurance, insurance premiums, insurance payments, insurance money, insurance liability, insured events, insurance contracts.